2023
DOI: 10.7717/peerj.15618
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin supplementation during porcine oocyte maturation improves the developmental competence of parthenogenetic activation and cloned embryos

Abstract: Luteolin (Lut), a polyphenolic compound that belongs to the flavone subclass of flavonoids, possesses anti-inflammatory, cytoprotective, and antioxidant activities. However, little is known regarding its role in mammalian oocyte maturation. This study examined the effect of Lut supplementation during in vitro maturation (IVM) on oocyte maturation and subsequent developmental competence after somatic cell nuclear transfer (SCNT) in pigs. Lut supplementation significantly increased the proportions of complete cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Mitochondria, cellular powerhouses, play pivotal roles in a plethora of physiological processes, including oocyte maturation and embryonic development ( 56 ). However, obesity can lead to mitochondrial dysfunction.…”
Section: Molecular and Physiological Mechanismsmentioning
confidence: 99%
“…Mitochondria, cellular powerhouses, play pivotal roles in a plethora of physiological processes, including oocyte maturation and embryonic development ( 56 ). However, obesity can lead to mitochondrial dysfunction.…”
Section: Molecular and Physiological Mechanismsmentioning
confidence: 99%
“…Furthermore, LUT improved oocyte developmental capacity, enhanced mitochondrial active content and mitochondrial membrane potential, as well as alleviated reactive oxygen species, cytochrome c, and lysed caspase 3 levels, while upregulating GSH levels. LUT also improved the maturation of porcine oocytes (IVM medium, 38.5°C, 5% CO 2 ) by activating lipid metabolism (Jeong et al, 2023). Subsequent studies found that LUT downregulated the expression of ER stress protein GRP78 and lysosomal protein LAMP1, enhanced the level of Golgi complex protein GOLPH3, activated senescence of SIRT1 oocytes, and regulated the distribution and function of organelles (Xing et al, 2023).…”
Section: Bioactivities Of Lutmentioning
confidence: 99%